Cultivating Social Capital - Resilience Against Adversity - Vasconcelos, Thiago (Hannover : Regionales Bauen und Siedlungsplanung, Leibniz Universität Hannover, 2020)
Based upon the fieldtrip and context analysis developed during the Master Architecture and Extreme Environments at KADK Copenhagen, the work described in this paper explores the resilience of food supply system, connected to extreme scenario development and socio-political trends, largely impacted by climate changes in Alaska, USA. A specific design focus has been set in the city of Anchorage where the project Permabioreactor explores new modalities for combined cultivation of super-nutrients, such as Algae, which sequesters excess carbon dioxide. This results in activating a process of circular economy, by providing a source of food and alleviate the impact of onset permafrost thaw because of the warming climate. Introducing a critical discussion on how scenario building methodology could be a strategic tool for planning against uncertainty, the contribution deals with themes across food production and security, energy resources and population distributions and development.